2020
DOI: 10.1101/2020.04.16.20067421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-reported COVID-19 symptoms on Twitter: An analysis and a research resource

Abstract: ObjectiveTo mine Twitter to quantitatively analyze COVID-19 symptoms self-reported by users, compare symptom distributions against clinical studies, and create a symptom lexicon for the research community. Materials and methodsWe retrieved tweets using COVID-19-related keywords, and performed several layers of semi-automatic filtering to curate self-reports of positive-tested users. We extracted COVID-19-related symptoms mentioned by the users, mapped them to standard IDs, and compared the distributions with m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 17 publications
4
40
0
1
Order By: Relevance
“…For a more detailed analysis of the tweets, the emotional quotients associated with the tweets were analyzed. Sentiment analysis using the National Research Council (NRC) sentiment lexicon enabled us to examine the expression of 10 terms related to basic emotions: anger , anticipation , disgust , fear , joy , negative , positive , sadness , surprise , and trust [ 26 , 27 ]. The terms positive and negative were removed because they are classifications and do not indicate positive or negative emotions; also, emotions (eg, fear or joy) are indicated by the NRC sentiment lexicon.…”
Section: Methodsmentioning
confidence: 99%
“…For a more detailed analysis of the tweets, the emotional quotients associated with the tweets were analyzed. Sentiment analysis using the National Research Council (NRC) sentiment lexicon enabled us to examine the expression of 10 terms related to basic emotions: anger , anticipation , disgust , fear , joy , negative , positive , sadness , surprise , and trust [ 26 , 27 ]. The terms positive and negative were removed because they are classifications and do not indicate positive or negative emotions; also, emotions (eg, fear or joy) are indicated by the NRC sentiment lexicon.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we compared the symptom prevalence of our study to the one provided by Sarker et al [ 5 ], in order to assess similarities and differences in COVID-19 symptoms experienced by different populations. As seen in Table 5 and Figure 5 , our findings complement those of Sarker et al [ 5 ] (correlation coefficient=0.72).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Twitter has been a source of data for many health and medical studies, such as surveillance and monitoring of flu and cancer timelines and distribution across the United States [ 1 ], analyzing the spread of influenza in the United Arab Emirates based on geotagged tweets in Arabic [ 2 ], and the surveillance and monitoring of influenza in the United Arab Emirates based on tweets in Arabic and English [ 3 ]. In addition, Twitter data have been utilized in symptom and disease identification in Saudi Arabia [ 4 ], and most recently, to examine COVID-19 symptoms as reported on Twitter [ 5 ] and to analyze the chronological and geographical distribution of infected tweeters in the United States [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sarker et al [88] mined Twitter to analyze symptoms of COVID-19 from self-reported users. The authors identified 203 COVID-19 patients while searching Twitter streaming API with expressions related to self-report of COVID-19.…”
Section: Social Media Datamentioning
confidence: 99%